The Role of Village Government in Providing Public Services to the Community in Galangpengampon Village, Wonopringgo District, Pekalongan Regency - Zakiyah, Nur; Sunarya, Amud (Yayasan Ilomata, 2024)
Public service is at the core of government administration, and providing quality service is key to assessing the performance of an institution. Village governments, as direct service providers, are expected to deliver professional and efficient services by law number 6 of 2014 to improve the welfare of the community. However, several obstacles such as the lack of effectiveness and efficiency in service delivery have led to dissatisfaction among the public. This research aims to analyze the supporting and inhibiting factors for the role of the Village Government in Providing Public Services to the Community in Galangpengampon Village, Wonopringgo District, Pekalongan Regency. The method used is descriptive qualitative with analysis tools, uses an interactive analysis model through a selection or reduction model, namely summarizing data obtained through direct contact with informants, events and situations at the research location. The real implication of this research is to find out what factors support and hinder the role of the Village Government in Providing Public Services to the Community in Galangpengampon Village, Wonopringgo District, Pekalongan Regency. So that way it can provide input for the village to improve services to the community. The results indicate that village governments play a role as mobilizers, facilitators, and regulators in improving public services, with cooperation among officials and community participation as supporting factors, while working conditions, infrastructure limitations, and the quality of human resources serve as inhibiting factors.